Investigation of the Dynamic Performance of a Large-Span Suspension Bridge Influenced by Scouring Based on Vehicle-Bridge Coupled Vibration - Qingfei Gao; Biao Wu; Renzhi Wang; Jiaqiang Zhang; Binqiang Guo; Jun Li (Shock and Vibration)
To study the damage of bridge pile foundations caused by scouring, two damage mechanisms of scouring are proposed in this paper. Considering the vehicle-bridge coupled vibration in terms of two aspects of the scouring depth and erosion depth, the vertical and transversal dynamic characteristics and dynamic responses of the bridge are studied under different cases for the most sensitive vehicle speed. The dynamic characteristics include the 1st and 2nd vibration modes of the vertical and transversal directions of the bridge. The dynamic responses include the vertical and transversal dynamic load allowances and acceleration of the bridge. The souring depth is more sensitive than the erosion depth, and the 2nd vertical mode is most substantially influenced by scouring and erosion. Because of the small value of the natural frequency of the vertical vibration modes, the transversal vibration modes may be more convenient to obtain. The study of the dynamic responses shows that the scouring depth can be represented by the dynamic load allowance in the middle of the span’s section and the erosion depth can be characterized by the dynamic load allowance at the quarter location of the span’s section.